ChemInform Abstract: Synthesis of 9H‐Pyrrolo[1, 2‐a]indole and 3H‐Pyrrolizine Derivatives via a Phosphine‐Catalyzed Umpolung Addition/Intramolecular Wittig Reaction. Issue 40 (September 2016) - Saleh, Nidal; Voituriez, Arnaud
Abstract: Optimized reaction conditions are developed for the title process allowing cyclization reactions of heteroaryl aldehydes (I) or (IV) with acetylene dicarboxylate (II) to form the title products in high yields.